(3CMcGe GdJMQT GdLfSj (B:s ((3OQGSI ebGQfI(B) /s - (3GdYHO GdefYe, YHO GdYRjR Hf SYOhfs ((3GdQjGV (B:s (3OGQ GdcJGH GdLGeYj,s, 2017)
(3Ef ef Mb GdTQjYI YdjfG Cf fagegG hef agegG eYQaI ebGUOgG hef ebGUOgG MaX GdVQhQjGJ GdJj LGAJ HgG GdTQjYI dUdGM GdfGS aj eYGTge heYGOge hgj (B: ((3GdOjf hGdfaS hGdYbd hGdeGd hGdY`QV(B) (3hGdJj dGHO efgG aj bjGe eUGdM GdOjf hNdd hcPdc JahJ hGdOfjG ; HMjK EPG abOJ de JSJbe eUGdM GdOfjG Hd JUjQ Edi aSGO GdSYGOI GdCNQhjI HahGJ GdfLGI hGdfYje, hMUhd GdNSQGf GdeHjf fJjLI GNJdGd MaX gPg KdGK BjGJ aj GdVQhQjGJ(B.s
(3GdeMJhjGJ (B: (3GdaUd GdChd (B: (3UhQ GdJMQT GdLfSj hCSHGHg hHjGf Mceg, GdeHMK GdChd (B: (3UhQ GdJMQT GdLfSj, GdeHMK GdKGfj (B: (3CSHGH GdJMQT GdLfSj, GdeHMK GdKGdK (B: (3Mce GdJMQT GdLfSj(B-(3GdaUd GdKGfj (B: (3EKHGJ GdJMQT GdLfSj, GdaUd GdChd (B: (3GdEbQGQ, GdeHMK GdKGfj (B: (3GdHjFI(B-(3GdaUd GdKGdK (B: (3YbhHGJ GdJMQT GdLfSj aj eTQhY GdfXGe hehba Gdabg GdESdGej efgG hHYV GdJWHjbGJ GdbVGFjI, GdeHMK GdChd (B: (3YbhHGJ GdJMQT GdLfSj aj eTQhY GdfXGe GdSYhOj, GdeHMK GdKGfj (B: (3ehba Gdabg ef YbhHGJ GdJMQT GdLfSj(B.s
(3cTGaGJ (B: (3UaMI (B267-280.s
(3edGMb (B: (3UaMI (B231-247.s
(3HHdjhLQGajI (B: (3UaMI (B248-266.s
Keywords: (3GdJMQT GdLfSjs -- (3bhGfjf hJTQjYGJs; (3GdJMQT GdLfSj (B((3abg ESdGej(B)s; (3GdLQGFe GdLfSjI s; (3GdLQGFe GdeNdI HGdTQas; (3LQGFe GdGYJOGA Ydi GdCTNGUs; (3GdLQjeI hGdeLQehfs